Co-trimoxazole-induced hypoglycaemia in an immunosuppressed intensive care patient. (February 2017) - Richards, Katherine A; Raby, Simon
An 18-year-old female inpatient on a neurosciences intensive care unitwith new onset super-refractory epilepsy became hypoglycaemic 48 h after commencing co-trimoxazole. She had been placed on this for prophylaxis against Pneumocystis jiroveci infection in the context of significant immunosuppression with high-dose corticosteroid therapy. In order to maintain glucose control, she required a continuous infusion of 10% dextrose at rates of 15–25 ml/h. Recurrent attempts to wean this were limited by further hypoglycaemia, until she spontaneously regained normoglycaemia after 73 days. This case report will discuss this unusual case of refractory hypoglycaemia, and the proposed pathophysiology of hypoglycaemia related to co-trimoxazole therapy.